2015
DOI: 10.1177/1358863x14568135
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of catheter-based thrombolytic therapy for acute submassive and massive pulmonary embolism

Abstract: Catheter-based thrombolysis (CBT) is emerging as an option for acute pulmonary embolism (PE). Although prior studies have demonstrated improvement in right ventricular function, little data is available regarding clinical patient outcomes. Our institution adopted CBT as an option for patients with submassive and massive PE and we evaluated its effect on patient outcomes. Two hundred and twenty-one patients who presented to our institution with submassive and massive PE were analyzed over three years by time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…13 Similarly, George et al documented that CDT in 32 patients with massive PE was not associated with improvement in adverse clinical events compared to patients managed without CDT. 4 Ain et al conducted a single-center study and reported survival rates of 58.6% for high-risk PE following the initiation of ECMO, which supports our present data. 14 Meneveau et al conducted a multicenter retrospective analysis to evaluate the outcomes for ECMO use among 52 patients with high-risk PE, 15 reporting a 30-day mortality of 61.5% in patients who underwent ECMO, which was further decreased when surgical embolectomy was employed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13 Similarly, George et al documented that CDT in 32 patients with massive PE was not associated with improvement in adverse clinical events compared to patients managed without CDT. 4 Ain et al conducted a single-center study and reported survival rates of 58.6% for high-risk PE following the initiation of ECMO, which supports our present data. 14 Meneveau et al conducted a multicenter retrospective analysis to evaluate the outcomes for ECMO use among 52 patients with high-risk PE, 15 reporting a 30-day mortality of 61.5% in patients who underwent ECMO, which was further decreased when surgical embolectomy was employed.…”
Section: Discussionsupporting
confidence: 91%
“…3 Despite advances in the therapeutic armamentarium, including systemic thrombolytic agents, catheter-directed therapies (CDT), and surgical embolectomy, many patients remain refractory to treatment. 4 Venous-arterial extra-corporeal membrane oxygenation (VA-ECMO) is a promising treatment modality to unload the acutely failing right ventricle (RV). 5 The use of ECMO for high-risk PE has been evaluated only in case series or small retrospective analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Most have been retrospective analyses and, given lack of power, variations in methodology, and limited study population, no definitive conclusion can be derived on the beneficial role of ultrasound. 1518…”
Section: Discussionmentioning
confidence: 99%
“…Although this tool was constructed in a cohort of patients undergoing surgical embolectomy, its application to aggressive nonsurgical therapies (catheter-based or systemic thrombolysis) should also be evaluated to potentially avoid ineffective and possibly harmful interventions. 19,20…”
Section: Commentmentioning
confidence: 99%